Evaluation of the oral health condition of schoolchildren in the south of Brazil. (30th September 2020) - Fonseca, V; Machado, V; Ribeiro, S; Alves, M; Nacao, M
Abstract: In order to subsidize policies, actions and intersectoral strategies for health promotion, protection and recovery, it is important to establish the distribution of oral diseases in the target population. Thus, the present study aims at identifying the oral health condition of students from a network of schools run by a Social Welfare, not-for-profit, non-governmental institution in Brazil's Southern Region. This is a census approved by a competent Research Ethics Committee, carried out in a school environment in 2018, involving 1, 243 children, 1, 172 of which at 5 years old and 71 at 12 years old. All had impacts on oral health and caries rates (dmf / DMFT), occlusion (Foster & Hamilton and DAI) and fluorosis (Dean) evaluated by properly trained and calibrated dentists.The most prevalent impact on oral health, at both ages, was "difficulty in eating". Students aged 12 and 5 years old showed, respectively, 0.28 and 1 tooth with caries experience; 5.8% and 5.3% with some need for treatment and a prevalence of malocclusion of 57.7% and 79%. Fluorosis was investigated only within the 12-year-old students and it was present in 26.8% of them. In view of the results, the planning of oral health actions in the schools of the social institution studied must privilege the actions of promotion, protection and recovery in the scope of malocclusions and strengthen those already implemented for caries disease. At the same time, a health surveillance system should be built and implemented for monitoring and assessment. Key messages: Identifying the epidemiological profile of the target population contributes to the efficient allocation of financial resources and the establishment of assertive strategies to meet their needs. Epidemiological surveys allow us to know the prevalence and severity of the disease, its distribution and treatment needs, allowing health planning and subsidizing the evaluation of services.